The effect of iodine therapy on future pregnancies in women with differentiated thyroid cancer: a review article - Atiyeh Mohamadzade Vatanchi; Narjes i Ayat; Ramin Sadeghi; Leila Pourali; Seyed Rasoul Zakavi; Atiyeh Zade Kaffash (Mashhad University of Medical Sciences, 2018)
Introduction: Iodine therapy after surgery is the gold standard treatment in patients with differentiated thyroid cancer. It is important to evaluate the effect of this treatment on future pregnancies of women who received iodine therapy. This review article was performed with aim to evaluate the pregnancy complications in patients who received iodine therapy with diagnosis of DTC. Methods: In this nonsystematic explanatory review article, three medical databases including ISI Web of Knowledge, Pubmed and Google Scholar were searched for related articles with the keywords of: thyroid AND (carcinoma OR cancer OR neoplasm) AND (iodine OR 131 OR radioiodine) AND (pregnan* OR labor OR parity OR gravid*). The English articles which published from 1950 were searched. Review articles, case reports and cross-sectional studies were excluded. Finally 7 articles included in the review. Results: Based on the 7 relevant studies, intrauterine fetal death, preterm labor, congenital malformation, low birth weight and neonatal death at first year of birth were similar in the studied groups. However, the differences between the studied groups in some studies were related to total number of abortions, induced abortions and lower incidence of live birth. Conclusion: The risk of pregnancy complications is not higher in women who received iodine therapy. The lower incidence of live birth and higher incidence of induced abortion in some studies can be related to mental and psychological effect of fear of iodine therapy impact on pregnancy in patient, physician, or the people around her.